Phytochemical and pharmacological profile of Kaduk (Piper sarmentosum Roxb.) - Ghazali, Nor Farahiyah; Mohd, Muzaida Aminah; Ibrahim, Maizatul Akma; Tengku Muhammad, Tengku Sifzizul (Malayan Nature Society, 2018)
Piper sarmentosum Roxb. (Piperaceae) is a medicinal herb. It is known as ‘kaduk’ and commonly found in subtropical and tropical regions of the world. This plant is traditionally used to cure various ailments and disease such as toothaches, headaches, fever, coughs and asthma. A wide range of phytochemical constituents have been isolated from this plant, including unsaturated amides, flavonoids, lignans, aristolactams, terpenes, steroids, prophenylphenols, alkaloids, long and short chain esters. It is well known to possess many potential bioactivities, for instance, as an antioxidant, anticancer, anti-tuberculosis, antimicrobial, anti-fungal, anti-plasmoid and anti-nociceptive plant. This paper summarizes the information related to the phytochemistry and pharmacology of P. sarmentosum with the description of its botany and traditional uses.